Nivolumab-Induced Subcutaneous Fat Necrosis: Another FDG-Avid Immune-Related Adverse Event. (February 2020) - Bhargava, Peeyush; Flynt, Lesley; Marcal, Leonardo
Abstract : Abstract: A 59-year-old woman with history of metastatic melanoma, currently on nivolumab, presents for a restaging FDG PET/CT scan. New subcutaneous hypermetabolic foci are seen in bilateral lower extremities, suggestive of recurrent melanoma. She is referred for percutaneous image-guided biopsy for definitive diagnosis of progressive disease. Ultrasound shows the subcutaneous foci to be hyperechoic (fat density), and biopsy of the right thigh nodule shows fat necrosis with no evidence of tumor. Fat necrosis, an immune-related adverse event, can be FDG-avid and mimic malignancy on PET/CT scan.